"Solid Emulsion": Gas‐Switchable Latex System with Reversible Coagulability and Redispersibility. (22nd June 2017) - Fang, Tommy; Wan, Zhengyi; Huo, Meng; Yuan, Jinying
Abstract : The ability to reversibly switch between latex solution and dried powder can potentially provide major economic and environmental benefits to emulsion related industries, especially in the substantial reduction of energy consumption and cost from the transportation and handling of latex water content. Here, a versatile CO2 /N2 ‐switchable latex system with high reversibility is developed by combining a CO2 ‐responsive polymeric surfactant and a CO2 ‐responsive initiator. In particular, the coagulability from latexes to dried powder and redispersibility back to solution form are systematically examined, showing minimal changes in the recovered latex particle size, distribution, morphology, and ζ‐potential for powder samples both freshly dried and after three months storage under ambient conditions. Hence, such a gas‐switchable "solid emulsion" system with long‐term storage stability and versatility in emulsion copolymerization monomer selection can potentially make significant industrial contribution and advancement. Abstract : A CO2 /N2 ‐switchable latex system is developed with facile coagulability into dried powder form, high redispersibility back to solution form, versatility in emulsion copolymerization monomer selection and long‐term storage stability, which can potentially provide significant economic and environmental benefits to emulsion related industries.